1992
DOI: 10.4319/lo.1992.37.1.0014
|View full text |Cite
|
Sign up to set email alerts
|

Prey capture by the four larval instars of Chaoborus crystallinus

Abstract: Prey capture ability of fourth-instar Chaoborus larvae has been studied widely but relatively little comparable information is available for the first three larval instars. In this laboratory study I measured strike and contact efficiencies of all four instars of Chaoborus crystallinus. The effectiveness of prey escape behavior was also recorded. As larval size increased the size of successfully captured and ingested prey also increased. There was no loss of ability to ingest the smallest prey by the largest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 21 publications
2
64
0
1
Order By: Relevance
“…Luecke and O'Brien (1983) showed that H. septentrionalis ate Ͼ10 times more small prey than large prey and almost 100 times more of the small-bodied B. longirostris than the large-bodied D. middendorffiana. We found D. middendorffiana to be positively associated with Chaoborus, likely because the adults of D. middendorffiana are essentially immune from Chaoborus predation because of gape limitation in Chaoborus (Swift 1992).…”
Section: Discussionmentioning
confidence: 79%
“…Luecke and O'Brien (1983) showed that H. septentrionalis ate Ͼ10 times more small prey than large prey and almost 100 times more of the small-bodied B. longirostris than the large-bodied D. middendorffiana. We found D. middendorffiana to be positively associated with Chaoborus, likely because the adults of D. middendorffiana are essentially immune from Chaoborus predation because of gape limitation in Chaoborus (Swift 1992).…”
Section: Discussionmentioning
confidence: 79%
“…Further, the threat to Daphnia will likely increase as the number of low calcium lakes increases in response to logging cycles and ongoing changes in atmospheric acid deposition (35). These changes will be long lasting as there is no reason to assume a negative feedback of the loss of daphniids on Chaoborus (potentially leading to a cycling of predator and prey) because this predator can simply switch to other taxa once the daphniids are gone (8,10,36).…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability of D. pulex to these gape-limited predators is largely determined by three morphological features of this animal: body size, neck spines, and carapace rigidity, each of which is influenced by the presence of predator kairomones and may be affected by the calcium concentration in the lake or pond. Daphnia body size plays a critical role in its vulnerability to Chaoborus, because prey whose size exceeds the mouth gape diameter of this predator are difficult to ingest (10). This results in a linear decrease in Chaoborus strike efficiency (probability of ingestion of prey following an attack) with increasing Daphnia body length (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Le taux de rencontre proie-prédateur (Giguerre et al 1982) dépend essentiellement de la densité des populations et surtout de la vitesse de nage des proies (Pastorok 1981). Quant à l'aptitude de ces dernières à échap-per à leur prédateur, elle est tributaire de la possession ou non de défenses antiprédation pré-ou post-contact (Walton 1988, Parejko 1991, Swift 1992. Riessen et al (1984) ont analysé les composantes de l'acte de préda-tion des larves de Chaoborus jusqu'à la deuxième attaque incluse et ont calculé la vulnérabilité de diverses proies.…”
Section: Discussion Et Conclusionunclassified